1999
DOI: 10.1002/hep.510300112
|View full text |Cite
|
Sign up to set email alerts
|

Systemic and splanchnic hemodynamic changes after liver transplantation for cirrhosis: A long-term prospective study

Abstract: The effect of orthotopic liver transplantation (OLT) on the systemic and splanchnic hemodynamic alterations of cirrhosis is still largely unknown. The aim of this study was to prospectively investigate the long-term changes induced by OLT on several hemodynamic parameters. In 28 patients undergoing OLT for cirrhosis, the following parameters were measured before surgery and subsequently at 6-month intervals (mean follow-up period, 17 months): cardiac index, mean arterial pressure (MAP), heart rate, total perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
94
2
7

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(106 citation statements)
references
References 44 publications
3
94
2
7
Order By: Relevance
“…It has been suggested that in cases of splenomegaly, the structural changes in the spleen, including fibrosis and hyperplasia, do not allow the complete return to normal size following normalization of portal hypertension after LT (2,4) . Thus, some degree of splenomegaly and thrombocytopenia persists in a significant number of patients who have been subjected to LT (12) . The findings of this and other studies have clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that in cases of splenomegaly, the structural changes in the spleen, including fibrosis and hyperplasia, do not allow the complete return to normal size following normalization of portal hypertension after LT (2,4) . Thus, some degree of splenomegaly and thrombocytopenia persists in a significant number of patients who have been subjected to LT (12) . The findings of this and other studies have clinical importance.…”
Section: Discussionmentioning
confidence: 99%
“…16 During liver transplantation, these alterations are maintained, but they tend to disappear during the following months. [17][18][19] This hyperdynamic state has not been a serious problem in cadaveric liver transplantation, in which a whole organ is placed orthotopically.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, subsequent to liver transplantation, renal sodium excretion and hemodynamic abnormalities normalize within 1 mo, and renal resistive indices decrease to normal values during the first posttransplantation year (131,132). Survival of patients with type 2 HRS is sufficiently prolonged to enable them to receive a liver transplant; however, the clinical applicability of transplantation in patients with type 1 HRS is limited by their shortened survival expectancy and long waiting times.…”
Section: Liver Transplantationmentioning
confidence: 99%